Corporate Governance Country Assessment : Czech Republic - World Bank (Washington, DC, 2013)
The Czech securities markets are rapidly evolving under political and commercial pressures. However, shortcomings remain that undercut their role in price discovery, and limit their value as risk diversification, as a source of finance and a mechanism for good corporate governance. Ownership concentration resulting from privatization in the early 1990s was accompanied by opaque deals and price manipulation, and owners often exploited control and acted against the interests of enterprises, creditors and minority shareholders. The policy recommendations may be grouped into three broad categories: legislative reform, institutional strengthening, and voluntary/private initiatives. In 2001, the Czech Republic instituted broad financial regulatory reforms. However, related party transactions, insolvency and more technical issues, such as voting by mail and shareholder meetings, still require more attention. Institutional strengthening is also vital to improve enforcement. The judiciary, Securities Commission, and other institutions that oversee financial market participants should be strengthened. Finally, in the area of voluntary/private initiatives, this report recommends enhanced training opportunities for Czech directors.